2013
DOI: 10.7567/jjap.52.126503
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of New Polishing Mechanism Based on Feret's Diameter of Contact Area between Polishing Pad and Wafer

Abstract: Relationships between pad surface characteristics and polishing rate are investigated. New parameter “total Feret's diameter” of contact portions is proposed as a key parameter, which shows simple correlation to the polishing rate. Feret's diameter is a projection length of a contact shape. Based on Feret's diameter, a new polishing model is proposed in which material is removed by abrasive particles existing at periphery of the pad contact portions, not on them. When a pad contact portion moves on a wafer, ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In this study, to explain the different effects of PS/CeO 2 and CeO 2 on polishing quality, the S 0 and the δ w were quantitatively calculated based on the contact-area theory 55,56 and the indentationdepth theory, 57 respectively. Table I shows that compared with CeO 2 , PS/CeO 2 could result in a larger contact area (because of the lower Young's modulus of PS/CeO 2 ) but larger indentation depth (due to the little size of CeO 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, to explain the different effects of PS/CeO 2 and CeO 2 on polishing quality, the S 0 and the δ w were quantitatively calculated based on the contact-area theory 55,56 and the indentationdepth theory, 57 respectively. Table I shows that compared with CeO 2 , PS/CeO 2 could result in a larger contact area (because of the lower Young's modulus of PS/CeO 2 ) but larger indentation depth (due to the little size of CeO 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of the in situ observation of the polishing efficiency was confirmed by the polishing experiment with a polishing pad. According to Isobe's polishing model [136], they suggested that the in situ detection of instantaneous temperature variations depending on Feret's diameters of the contact area between the pad and the wafer, leading to higher material removal rate [131]. As they mentioned, it is very difficult to directly measure the change in the temperature at the particlewafer-pad interface due to the limitation of the proposed method.…”
Section: Number Of Particles Particle Velocitymentioning
confidence: 99%
“…As shown in Fig. 16 (a), the abrasives are accumulated due to the friction against the wafer (Boumyoung Park, et al, 2009) (Xuesong Han, et al, 2009 and the accumulated abrasives effectively work for polishing at the actual contact points (Akira Isobe, et al, 2013). On the other hand, Fig.…”
Section: Effects Of Slurry Film Thickness At the Contact Interface Onmentioning
confidence: 99%